2003
DOI: 10.1021/ma034147x
|View full text |Cite
|
Sign up to set email alerts
|

NMR Studies of the Effect of Adsorbed Water on Polyelectrolyte Multilayer Films in the Solid State

Abstract: Fast-MAS 1 H NMR is used to probe the structure and dynamics of the adsorbed water and polymer components in polyelectrolyte multilayer (PEM) films and the bulk polyelectrolyte complex (PEC). The films, ranging in size from a single layer to 5 bilayers, consist of poly(diallyl dimethylammonium chloride), PDADMAC, and poly(sodium-4-styrenesulfonate), PSS, adsorbed onto colloidal silica. Relaxation and line width measurements show that the adsorbed water is less mobile in the films than in the analogous PEC. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 35 publications
(97 reference statements)
2
96
1
Order By: Relevance
“…The strongly dipolar character (nonzero γ + ) of the swollen films is a clear sign of greater hydration. These results fit very well with data obtained in NMR studies of the effect of adsorbed water on polyelectrolyte multilayers [36]. The NMR data clearly showed that water adsorbed in PDADMAC/PSS multilayers is mainly associated with the more hydrophilic PSS chains and less water is associated with the PDADMAC chains.…”
Section: "Hydrophobization" Effectsupporting
confidence: 88%
“…The strongly dipolar character (nonzero γ + ) of the swollen films is a clear sign of greater hydration. These results fit very well with data obtained in NMR studies of the effect of adsorbed water on polyelectrolyte multilayers [36]. The NMR data clearly showed that water adsorbed in PDADMAC/PSS multilayers is mainly associated with the more hydrophilic PSS chains and less water is associated with the PDADMAC chains.…”
Section: "Hydrophobization" Effectsupporting
confidence: 88%
“…Their alternately assembled PSS/PDAD-MAC multilayers have a T g of 35-40 8C when they are fully hydrated in water, which functions as a plasticizer and thereby increases the polymer mobility. [57,58] According to the result of Figure 3a, an apparent transition occurred at about 40 8C, after which the pattern height increased in a faster rate. This is indicative of the T g of the PSS/PDADMAC multilayers, which is consistent with previous values measured by other methods.…”
Section: Influence Of Molding Temperaturementioning
confidence: 91%
“…[8][9][10][11][12][13][14][15][16] Fast magic-angle spinning (30-60 kHz) is vital, as it provides excellent resolution of resonances, particularly in the hydrogen bonding region. Additionally, variable temperature measurements can be used to establish linewidth trends, and correlations to proton dynamics.…”
Section: Nmr Methodologymentioning
confidence: 99%